Effects of ultrasound-guided transversus abdominis plane block with combined dexmedetomidine and dexamethasone on the stress and immune function - Changsheng Su; Guoshao Zhu; Zhenming Kang; Shunyuan Li; Wenqin Xie (BMC Anesthesiology)
Abstract Background Ultrasound-guided transversus abdominis plane (TAP) block is widely used to provide effective postoperative analgesia and facilitate enhanced recovery after laparoscopic radical colectomy. However, the duration of TAP block is often limited by the pharmacokinetics of local anesthetics, and evidence regarding optimal adjuvant combinations to prolong its efficacy remains scarce. Methods In this prospective, randomized controlled trial, 160 patients undergoing elective laparoscopic colectomy were randomly assigned to four groups (n = 40 each): Control (ropivacaine alone), Dexmedetomidine group (ropivacaine + dexmedetomidine), Dexamethasone group (ropivacaine + dexamethasone), and Combination group (ropivacaine + dexmedetomidine + dexamethasone). Primary outcomes included postoperative pain scores and sufentanil consumption. Secondary outcomes included Ramsay Sedation Scores, CD4+/CD8 + T cell ratios, and serum markers of stress response. Results Compared to ropivacaine alone, both dexmedetomidine and dexamethasone as single adjuvants significantly reduced postoperative pain scores and opioid requirements (p < 0.05). The combination group exhibited the most prolonged analgesic effect, with significantly lower sufentanil consumption and higher sedation scores at 6 and 24 h (p < 0.01). Moreover, both adjuvants attenuated the postoperative decline in CD4+/CD8 + T cell ratio, and the combination group demonstrated the greatest preservation of immune function and suppression of stress-induced immunosuppression. Conclusions The combination of dexmedetomidine and dexamethasone as adjuvants to ropivacaine in TAP block provides superior and prolonged analgesia, reduces opioid consumption, and offers additional immunomodulatory benefits. This strategy represents a promising enhancement to multimodal analgesia protocols for patients undergoing laparoscopic colectomy. Trial registration The study was registered in Chinese Clinical Trial Registry (ChiCTR2200065816, 2022-11-16).